Алгоритми автоматичної генерації лабиринтів - Сухоцкая, А. В. (ХНУРЕ, 2020)
In this paper described: the algorithms for generating random labyrinths, that can be used to diversify the design of the levels, to adapt the design to subject of your game, to add other objects for the diversification and complexity of the game layout. This is research about different algorithms, analyzing their effectiveness, comparing their opportunities for needs of different customers or tasks. It could be useful in game industry, as well as in real life, for example for architecture and designing of buildings